Analysis of the quality factor of micro-beam resonators based on heat conduction model with a single delay term - Kumar H.; Mukhopadhyay S. (My University, 2025)
The present article investigates the quality factor of thermoelastic damping in micro-beam resonator from the standpoint of a very recent thermoelasticity theory proposed by Quintanilla (2011). In recent years, significant attention is being paid to micro- and nano-resonators due to their wide applications in micro- and nano-electromechanical systems (MEMS/NEMS). The quality performance of a micro-beam resonator is usually measured by the quality factor and thermoelastic damping is considered to be the most important intrinsic dissipative mechanism in micro and nanoscale devices. In the present article, we consider the heat conduction model with a single delay term given by Quintanilla (2011) and derive an expression for thermoelastic damping by applying complex frequency approach. The variation of thermoelastic damping versus normalized frequency and thickness of Silicon micro-beam resonator for different aspect ratios have been studied. We compare the results of present model with the corresponding results of thermoelasticity theories of type GN-III, three-phase-lag (TPL), and Lord-Shulman (LS) models and investigate that the new model with a single delay term (NMSDT) gives high Q-factor of the micro-beam resonator’s sensitivity in comparison to LS and TPL models and the results under this model have more similarity to the results of GN-III model. © 2019, © 2019 Taylor & Francis Group, LLC.